2004
DOI: 10.2337/diabetes.53.9.2375
|View full text |Cite
|
Sign up to set email alerts
|

Effect of a High-Protein, Low-Carbohydrate Diet on Blood Glucose Control in People With Type 2 Diabetes

Abstract: There has been interest in the effect of various types and amounts of dietary carbohydrates and proteins on blood glucose. On the basis of our previous data, we designed a high-protein/low-carbohydrate, weight-maintaining, nonketogenic diet. Its effect on glucose control in people with untreated type 2 diabetes was determined. We refer to this as a low-biologically-availableglucose (LoBAG) diet. Eight men were studied using a randomized 5-week crossover design with a 5-week washout period. The carbohydrate:pro… Show more

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
2
1
1
1

Citation Types

14
257
4
6

Year Published

2005
2005
2024
2024

Publication Types

Select...
6
4

Relationship

0
10

Authors

Journals

citations
Cited by 363 publications
(282 citation statements)
references
References 26 publications
(27 reference statements)
14
257
4
6
Order By: Relevance
“…Small, short-term studies in diabetes suggest that diets with protein content Ͼ20% of total energy reduce glucose and insulin concentrations, reduce appetite, and increase satiety (68,69). However, the effects of high-protein diets on longterm regulation of energy intake, satiety, weight, and the ability of individuals to follow such diets long term have not been adequately studied.…”
Section: Nutrition Recommendations and Interventionsmentioning
confidence: 99%
“…Small, short-term studies in diabetes suggest that diets with protein content Ͼ20% of total energy reduce glucose and insulin concentrations, reduce appetite, and increase satiety (68,69). However, the effects of high-protein diets on longterm regulation of energy intake, satiety, weight, and the ability of individuals to follow such diets long term have not been adequately studied.…”
Section: Nutrition Recommendations and Interventionsmentioning
confidence: 99%
“…Alterations of these factors were associated with expressions of 12 selenoproteins (1,3,5,9,18,19). However, to the best of our knowledge, there was no information on effects of dietary selenium, in particular high selenium intake, on body protein metabolism, although protein synthesis was reported to negatively regulate insulin sensitivity (20,21) and a high protein diet inhibited the development of type 2 diabetes (22). Mammalian target of rapamycin (mTOR), ribosomal protein S6 kinase (P70), ribosomal protein S6 (S6), factor 4E binding protein 1 (4EBP1), and eukaryotic translation initiation factor 4E (EIF4E) are key factors involved in the protein synthesis pathway (23)(24)(25)(26)(27).…”
Section: Introductionmentioning
confidence: 80%
“…Increasing the amount of dietary protein has been suggested to increase satiety and reduce total energy intake, thereby stimulating weight loss (Halton and Hu, 2004). In a prolonged intervention study, Gannon and Nuttall (2004) reported improved glycemic control over a 5-week intervention after increasing the protein content in the diet. Though this substantially improved glycohemoglobin levels, it should be noted that dietary protein intake was increased at the expense of carbohydrate intake, thereby lowering postprandial blood glucose excursions.…”
Section: Discussionmentioning
confidence: 99%